PEA PROTEIN COATINGS INCORPORATED WITH PHENOLIC COMPOUNDS REDUCE OXIDATIVE RANCIDITY IN RAW HAZELNUTS (CORYLUS AVELLANA L.) - Camila, Perussello; Ivan, Milovanović; Belović, Miona; Dragana, Plavšić; Milica, Pojić; Brijesh, Tiwari (Food and Feed Research, 2024)
With the aim of producing a functional edible coating to delay rancidity in fat-rich foods, phenolics were extracted from apple pomace and incorporated into 10%-aqueous solutions of pea protein at mass percentages ranging from 0% to 5%. Hazelnuts were coated with these solutions, dried under laminar air flow, vacuum-packed in polypropylene bags and stored at room temperature for 14 days. The 5%-extract coatings increased the antioxidant activity of the hazelnuts by 30 times, while maintaining a texture akin to the uncoated product. The fatty acid profile of all samples remained unchanged during storage. Uncoated hazelnuts and those coated with the 1%-formulation showed detectable levels of hexanal (0.65 mg/kg and 0.31 mg/kg, respectively), a marker of lipid oxidation. In contrast, hexanal was not detected in the samples coated with the 2% and 5%-formulations, indicating a protective effect against lipid oxidation
Keywords: functional coating; antioxidant activity; hazelnuts; shelf life; lipid oxidation; fatty acids